Safety and immunogenicity of different Clostridioides (Clostridium) difficile vaccine formulations in two early phase randomized studies of healthy adults aged 50–85 years. Issue 40 (24th September 2021) - Lawrence, Jody; Kitchin, Nicholas; Anderson, Annaliesa S.; Pride, Michael W.; Jansen, Kathrin U.; Gruber, William C.; Peng, Yahong; Yi, Kevin; Knirsch, Charles; Webber, Chris
Highlights: Healthy adults received a toxoid-based C difficile vaccine alone or with QS-21. Phase 1 and 2 trials evaluated 2 dosing regimens (Days 1, 8, 30; Months 0, 1, 3). Studies were terminated due to grade 3 injection site redness postdose 2 (day regimen). Both vaccine formulations were immunogenic. Formulations discussed in this manuscript were not developed further. Abstract: Background: Two phase 1/phase 2 studies assessed 2 formulations of investigational bivalent Clostridioides (Clostridium) difficile vaccine (QS-21 adjuvanted toxoid and toxoid-alone) in healthy adults 50–85 years of age. Methods: The QS-21 adjuvanted toxoid vaccine study randomized subjects 3:1 to 100 μg QS-21–containing C difficile vaccine or placebo administered in a shortened-month (Months 0, 1, 3) or day (Days 1, 8, 30) regimen. The toxoid-alone vaccine study randomized subjects 3:3:1 to receive 100 or 200 μg unadjuvanted C difficile vaccine formulation or placebo in Stages 1 and 2 (sentinel cohorts of different age groups), and 3:1 to receive the selected dose of unadjuvanted C difficile vaccine formulation or placebo in Stage 3 (Days 1, 8, 30). Safety was the primary outcome for both studies. Immunogenicity was determined by measuring serum toxin A– and B–specific neutralizing antibodies. Results: In the day regimen, 10 reports across both studies of grade 3 injection site redness postdose 2 triggered predefined stopping rules. Local reactions in both studies were more common among vaccine versus placebo recipients. Injection site pain predominated and was generally mild in severity. Systemic events were infrequent and generally mild-to-moderate in severity. Adverse events were reported by 50.0%–75.0% and 16.7%–50.0% of subjects in the QS-21 and toxoid-alone studies, respectively. Immune responses peaked around Day 37 (shortened-month regimen) or between Day 15 and Month 2 (day regimen) and remained above baseline throughout follow-up. Conclusions: Both formulations demonstrated robust immunogenicity. Both studies stopped early due to grade 3 injection site redness postdose 2 of the day regimen; neither formulation progressed to later stage development. Instead, an aluminum hydroxide-containing formulation of the vaccine candidate administered at 0, 1, and 6 months, which was safe and immunogenic in phase 1 and 2 studies, advanced to phase 3 studies.